The Impact Model of Physical Factors on the Dynamics of Oxidative Transformations of Cold-pressed Oils - Kondratowicz-Pietruszka, Elżbieta; Ostasz, Lidia (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The objective of this research project was to determine the effect of high temperatures and UV irradiation on the dynamics of oxidation of selected cold-pressed oils. The composition of fatty acids in the oil samples and their characteristic numbers were determined. The oil samples were heated to temperatures of: 80, 100 and 110ºC without irradiation, and after UV irradiation. Measurements of the peroxide value during heating were used to determine the oxidation changes. It was determined that that value rose along with the temperature. The processes studied were characterised by varying dynamics, a fact confirmed by the values of rate constants and the ratios of these rate constants for comparable processes. Stability periods were calculated for oil samples heated at the three temperatures, and subjected to UV irradiation prior to heating. The tests demonstrated that both an increase in temperature and irradiation result in the oils having a clearly shorter stability period.